Disaster Mitigation of Tourism Destinations in the Megalithic Area of Lore Lindu National Park in Poso Regency, Central Sulawesi Province - Marzuki, Muhammad; Rusdin, Andi; Hatta, Ikhtiar; Hapsa, Hapsa; Badollahi, Muh Zainuddin (Pusat Studi Pembangunan dan Pemberdayaan, 2024)
This study aims to determine the efforts that have been made to minimize disasters with a structural/physical disaster mitigation approach through natural and/or artificial physical development, and to determine the efforts that have been made to reduce the impact of disasters with a non-structural/non-physical disaster mitigation approach through strengthening community capacity at tourist destinations in the megalithic area of Lore Lindu National Park in Poso Regency, Central Sulawesi Province. Data collection was carried out by field surveys, document reviews, and in-depth interviews. The method used is explorative descriptive analysis utilizing aspects contained in disaster mitigation in the megalithic area using qualitative methods using a phenomenological approach. This study will be conducted at megalithic tourist destinations in 3 valleys in Poso Regency, namely Bada Valley, Behoa Valley, and Napu Valley. Identifying with data triangulation techniques and interactive analysis based on 4 components of analysis, namely data collection, data reduction, data presentation, and drawing conclusions. The results of the study indicate that conditions in the field in the Megalithic area in Poso Regency indicate challenges that need to be overcome to improve safety, comfort, and tourism experience. Improvements to infrastructure, drainage systems, and evacuation signs and routes must be a priority, accompanied by increasing community preparedness for disaster risks.